China's Evolving Managerial Labor Market - Groves, Theodore; Hong, Yongmiao; McMillan, John; Naughton, Barry (Journal of Political Economy, 1995)
Recent reforms of Chinese state-owned enterprises strengthened a nascent managerial labor market by incorporating incentives suggestive of competitive Western labor markets. Poorly performing firms were more likely to have a new manager selected by auction, to be required to post a higher security deposit, and to be subject to more frequent review of the manager's contract. Managers could, be, and were, fired for poor performance. Managerial pay was linked to the firm's sales and profits, and reform strengthened the profit link and weakened the sales link. Thus the economic reforms helped develop an improved system of managerial resource allocation responsive to market forces.